1995
DOI: 10.1128/jcm.33.7.1856-1859.1995
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of Mycobacterium tuberculosis complex in respiratory specimens by Gen-Probe Amplified Mycobacterium Tuberculosis Direct Test and Roche Amplicor Mycobacterium Tuberculosis Test

Abstract: Two hundred and fifty-six sputum, bronchoalveolar lavage, and bronchial and tracheal aspirate specimens from 243 patients were tested for the presence of Mycobacterium tuberculosis complex by auramine fluorochrome staining, rRNA target amplification (Gen-Probe Amplified Mycobacterium Tuberculosis Direct Test [AMTD]), and PCR (Roche Amplicor Mycobacterium Tuberculosis Test [Amplicor PCR]). The results were compared with those of conventional Löwenstein-Jensen tube culture and BACTEC radiometric liquid culture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(43 citation statements)
references
References 19 publications
7
35
1
Order By: Relevance
“…The results were confirmed and were considered false negative, although two specimens showed a signal 20 times greater than that of the negative VOL. 35,1997 RAPID DETECTION OF M. TUBERCULOSIS BY LCR 1997 on July 10, 2020 by guest http://jcm.asm.org/ control (S/CO, 0.77 in both cases). These 18 specimens were from 14 patients, including 2 patients with multidrug-resistant TB.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The results were confirmed and were considered false negative, although two specimens showed a signal 20 times greater than that of the negative VOL. 35,1997 RAPID DETECTION OF M. TUBERCULOSIS BY LCR 1997 on July 10, 2020 by guest http://jcm.asm.org/ control (S/CO, 0.77 in both cases). These 18 specimens were from 14 patients, including 2 patients with multidrug-resistant TB.…”
Section: Resultsmentioning
confidence: 97%
“…Vuorinen et al (35) evaluated the Gen-Probe Amplified M. tuberculosis Direct Test (AMTDT) and Amplicor M. tuberculosis test (Roche Diagnostic Systems, Somerville, N.J.) with 256 respiratory specimens from 243 patients, with a positivity rate of 12.7% and a staining sensitivity of 76%. The sensitivities, specificities, PPVs, and NPVs were 86.2, 100, 100, and 98.2%, respectively, for AMTDT and 82.8, 100, 100, and 97.8%, respectively, for the Amplicor test.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 5000 specimens, there was a sensitivity of 83.5% and a specificity of 99% (6), and Carpentier et al reported 86% sensitivity and 98% specificity (5). The use of commercial techniques that increase standardization has led to comparable results from several different laboratories (16,18,28). For example, the results of one multicenter study, in which one of these techniques was evaluated in six different laboratories, show a sensitivity of 91.4% for samples with positive staining and 60.9%) for those with negative staining, with a specificity Reamplification techniques produce an increase in sensitivity and have been used to diagnose extrapulmonary tuberculosis (26), but they increase the possibility of cross-reactions since each PCR tube may contain up to 10l2 copies of an amplicon, and the smallest aerosolized drop may contain as many as lo5 copies of that amplicon.…”
Section: Discussionmentioning
confidence: 99%
“…The first two commercial tests used for the identification of Mycobacterium tuberculosis were the Amplicor Mycobacterium tuberculosis test (MTB; Roche Diagnostic Systems, Rotkreuz, Switzerland) and the Mycobacterium tuberculosis direct test (MTDT; Gen-Probe, Inc., San Diego, CA, USA). The average sensitivity and specificity of these assays were 70%-95% in clinical studies (Vuorinen et al, 1995;Dalovisio et al, 1996;Ichiyama et al, 1996). In a multicenter study, Noordhoek et al (1996) reported that results obtained with both methods were not reproducible, and mycobacterial detection from clinical specimens therefore required the development of reliable, standardized and automatized new methods were required.…”
Section: Discussionmentioning
confidence: 96%